Shaping the future of commercial quantum computer and the challenge for information security - Chao WANG; Yun-jiang WANG; Feng HU (网络与信息安全学报)
The progress on universal quantum computer devices is show, so that attacking the 1 024 bit RSA by Shor algorithm is impractical currently. The modern cryptography still has strong security. Take the quantum devices constraints into consideration was proposed for the first time, the storage of former registers in the Shor algorithm should be 100 or less Qubits theoretically decreased from 1 000 or more Qubits. Quantum artificial intelligence, as the rapid progress of special quantum computer, was regarded as the new generation computing idea which met the goal of national strategic computing initiative(NSCI). With the wide applications in the field of machine learning and artificial intelligence, importance to the influences of quantum artificial intelligence on the big data security on internet should be attached. Additionally, it was the first time to use the quantum computer for designing cryptography and it shed an interesting light on cryptography design based on the quantum artificial intelligence which had not been reported anywhere before.